Analisis Kebijakan Pemerintah Arab Saudi Menaikan Tarif Bea Masuk dan Implikasinya Terhadap Ekspor Indonesia - Ningsih, Rahayu; Nisaa', Choirin (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2021)
Saudi Arabia is Indonesian trading partner with a total trade value in 2019 reached USD 5.07 billion. Indonesia's trade with Saudi Arabia contributed to a deficit in Indonesia's trade balance, from USD 1.36 billion in 2015 to USD 3.68 billion in 2018. Amid efforts to increase exports to Saudi Arabia, on May 27, 2020, Custom Saudi, has issued a policy of changing the rate of import duty on 37 tarif lines (HS 2 digit) with an increase to be in the range of 7% to 20% from the initial rate, which is in the range of 5% to 12%. This matter, of course, has potential effect on Indonesia's export penetration. This analysis aims to identify Indonesian export products that are affected by the increase in import duty rates in Saudi Arabia and analyze the impact of the increase in the import duty of Saudi Arabia and its implications for Indonesia's export performance. With the descriptive analysis method using secondary data of trade data sourced from the Central Bureau of Statistics and UN Comtrade, this study concluded that the increase in Saudi Arabia's import duties on Indonesia's main export products had an impact on several of Indonesia's main export products, namely paper products, iron and steel products, iron and steel, Man-made staple fibres, and Machinery. Meanwhile, other export products such as automotive, plastic product, Electrical machinery, palm oil, processed meat and fish products, and some textile products have no substantial impact. Therefore, to anticipate the impact on the penetration of Indonesian export products, the government needs to disseminate information to business actors, especially exporters whose products are subject to an increase in import duty in Saudi Arabia so that anticipatory steps can be taken as well as efforts to find alternative export destination markets in other countries.